Phytoremediation as a viable ecological and socioeconomic management strategy - Phang, Lai Yee; Mingyuan, Lim; Mohammadi, Mitra; Tee, Chong Siang; Yuswan, Mohd Hafis; Cheng, Wan Hee; Lai, Kok Song (Springer, 2024)
Phytoremediation is an environmentally friendly alternative to traditional remediation technologies, notably for soil restoration and agricultural sustainability. This strategy makes use of marginal areas, incorporates biofortifcation processes, and expands crop alternatives. The ecological and economic benefts of phytoremediation are highlighted in this review. Native plant species provide cost-efective advantages and lower risks, while using invasive species to purify pollutants might be a potential solution to the dilemma of not removing them from the new habitat. Thus, strict management measures should be used to prevent the overgrowth of invasive species. The superior advantages of phytoremediation, including psychological and social improvements, make it a powerful tool for both successful cleanup and community well-being. Its ability to generate renewable biomass and adapt to a variety of uses strengthens its position in developing the bio-based economy. However, phytoremediation faces severe difculties such as complex site circumstances and stakeholder doubts. Overcoming these challenges necessitates a comprehensive approach that balances economic viability, environmental protection, and community welfare. Incorporating regulatory standards such as ASTM and ISO demonstrates a commitment to long-term environmental sustainability, while also providing advice for unique nation-specifc requirements. Finally, phytoremediation may contribute to a pleasant coexistence of human activity and the environment by navigating hurdles and embracing innovation.